Foreign body ingestion in children: an audit of transit time. Issue 6 (November 1998) - Macgregor, D; Ferguson, J
Abstract : OBJECTIVES: To study the pattern of ingestion of radio-opaque foreign bodies in children and to ascertain the average transit time to passage per rectum in order to rationalise future management. METHODS: This prospective study consisted of 100 children under the age of 14 years, presenting to the accident and emergency department of the Royal Aberdeen Children's Hospital having ingested a radio-opaque foreign body. All children had initial radiography and were subsequently followed up in an attempt to ascertain the transit time of the foreign body. RESULTS: The majority of ingestions (73%) were in younger children (5 years and under). The time taken to pass the foreign bodies per rectum varied greatly. Almost half were never recovered. Transit time appears to increase with age. Three children were given oral cisapride to increase gastric motility after prolonged retention in the stomach. CONCLUSIONS: Transit time is very variable and cannot be predicted. Sifting of the stools is unpleasant and unhelpful. Repeat radiography should not be encouraged as this results in unnecessary radiation. Cisapride may be useful in cases where there is prolonged retention of a foreign body in the stomach. There may be an indication for routine use of cisapride in all cases of ingested foreign bodies, however further audit would be required.